2016
DOI: 10.1007/s00405-016-3914-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure on arterial stiffness in patients with obstructive sleep apnea and hypertension: a meta-analysis

Abstract: Arterial stiffness has been recognized as a predictor of cardiovascular and all-cause mortality in hypertensive patients. However, the impact of continuous positive airway pressure (CPAP) on arterial stiffness in patients with OSA and hypertension remains inconclusive. We performed a meta-analysis to determine whether effective CPAP therapy could decrease arterial stiffness. Two reviewers independently searched PubMed, Embase, Web of Science and Cochrane Library prior to March 5, 2015. Information on character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Brachial ankle pulse wave velocity (baPWV), which is considered a surrogate marker of CVD, has been increasingly used in clinical as well as population-based studies owing to its simplicity and ease of measurement 8 . Unsurprisingly, substantial data from clinical or community-based studies demonstrated that pulse wave velocity (PWV) in patients with OSA is significantly high, but decreases after continuous positive airway pressure (CPAP) treatment 9 11 . Moreover, recent systemic reviews also revealed a significant association between OSA and PWV, suggesting that increased PWV might be an independent predictor of OSA-related cardiovascular complications 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Brachial ankle pulse wave velocity (baPWV), which is considered a surrogate marker of CVD, has been increasingly used in clinical as well as population-based studies owing to its simplicity and ease of measurement 8 . Unsurprisingly, substantial data from clinical or community-based studies demonstrated that pulse wave velocity (PWV) in patients with OSA is significantly high, but decreases after continuous positive airway pressure (CPAP) treatment 9 11 . Moreover, recent systemic reviews also revealed a significant association between OSA and PWV, suggesting that increased PWV might be an independent predictor of OSA-related cardiovascular complications 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…So, vascular stiffness may be a precursor rather than the result of hypertension. In our study we show that CPAP can improve arterial stiffness in patients with OSA and hypertension, and we speculated that it might be beneficial to delay or prevent the occurrence of cardiovascular disease in patients with OSA and hypertension [36]. As in the study of Kartali [28], the PWV is reduced at first night and further decreased after 3 months of treatment compared to baseline which implies that not only a functional, but also a structural change is taking place in the arteries..…”
Section: Discussionmentioning
confidence: 58%
“…There are at least two meta-analysis [ 6 , 7 ] identifying a decrease in arterial stiffness after CPAP treatment in patients with OSA, and in patients with OSA and hypertension; only four from the selected studies evaluated the effect on cf-PWV.…”
Section: Discussionmentioning
confidence: 99%
“…OSA is associated with increased arterial stiffness, with an improvement after continuous positive airway treatment (CPAP) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%